Kemampuan Komunikasi Peserta Didik Kelas VIII dalam Pembelajaran Berbasis Masalah Materi Persamaan Garis Lurus Menggunakan Soal AKM Numerasi - Vijjani, Chindy Octa; Meryansumayeka; Yusuf, Muhammad; Scristia, Scristia (SJME (Supremum Journal of Mathematics Education), 2024)
This research aims to analyze the communication skills of class VIII students in problem-based learning on even number equations using AKM Counting questions at SMPN 53 Palembang. The subjects of this research were class VIII students with high, medium and low levels of mathematics learning ability. This research uses a qualitative descriptive research type. Data was collected through written tests and deepened further through interviews. In general, the findings of this research indicate that the communication skills of Class VIII students at SMPN 53 Palembang are still relatively low. This is based on the results of tests carried out on 62 students who were research subjects, of which 21 students were in the good category, 6 students were in the medium category, and 35 students were in the good category, people in the lower category. Students in the good category have shown indicators of communication skills, students in the medium category have not shown indicators of communication skills, while students in the low category have not shown indicators of communication skills